c-JUN: a chromatin repressor that limits mesoderm differentiation in human pluripotent stem cells - Zhang, Ran; Li, Guihuan; Zhang, Qi; Wang, Zhenhua; Xiang, Dan; Zhang, Xiaofei; Chen, Jiekai; Hutchins, Andrew P; Qin, Dajiang; Su, Huanxing; Pei, Duanqing; Li, Dongwei (Nucleic acids research, 2025)
Cell fate determination at the chromatin level is not fully comprehended. Here, we report that c-JUN acts on chromatin loci to limit mesoderm cell fate specification as cells exit pluripotency. Although c-JUN is widely expressed across various cell types in early embryogenesis, it is not essential for maintaining pluripotency. Instead, it functions as a repressor to constrain mesoderm development while having a negligible impact on ectoderm differentiation. c-JUN interacts with MBD3–NuRD complex, which helps maintain chromatin in a low accessibility state at mesoderm-related genes during the differentiation of human pluripotent stem cells into mesoderm. Furthermore, c-JUN specifically inhibits the activation of key mesoderm factors, such as EOMES and GATA4. Knocking out c-JUN or inhibiting it with a JNK inhibitor can alleviate this suppression, promoting mesoderm cell differentiation. Consistently, knockdown of MBD3 enhances mesoderm generation, whereas MBD3 overexpression impedes it. Overexpressing c-JUN redirects differentiation toward a fibroblast-like lineage. Collectively, our findings suggest that c-JUN acts as a chromatin regulator to restrict the mesoderm cell fate.